(untitled) (Research, Society and Development, 2022)
Obesity is a problem that affects millions of people worldwide. It is a disease of multifactorial etiology, it is the result of a complex interaction between behavioral, cultural, genetic, physiological and psychological factors. Currently, it is a serious public health problem where there is a high percentage of treatment failure and relapses. The perception of the curative power of some plants is one of the forms of relationship between human populations and medicinal plants. Phytotherapy has shown positive effects under the prevention and treatment of several diseases, including obesity. Green tea (Camellia sinensis) contains flavonoid polyphenolic compounds. These substances found are known as catechins, highlighting epigallocatequine gallate. The objective of this research was to verify the properties presented by green tea that may contribute to the treatment of obesity. This is a qualitative bibliographic survey, using using scientific articles and books. The results obtained through in vitro and in vivo experiments point to green tea as a product that has properties capable of acting in the slimming process. The studies indicate that green tea may act mainly in increasing the production of body heat (thermogenesis), promoting greater energy expenditure. It has been observed that there is no determination of the dosage and the form of preparation of the tea that can ensure the achievement of the desired effects. We emphasize the importance of more studies for a better understanding of its bioactive effects.